3D printing amphiphilic graphene polymer composites for high performance applications - Wee, Jonathan Jianwei (Nanyang Technological University, 2024)
Karbohm (mGO) is a modified graphene oxide that encompasses the exceptional mechanical, thermal, and electrical properties of graphene which are typically lost when graphene is oxidised. This study explores the material development of mGO inks for extrusion-based direct ink writing by evaluating the use of ionic cross-linking as a gelation method for printing mGO inks, assessing the compatibility of mGO with CNC and CNF composites, and determining the optimal dispersion mechanism for both the ionically modified mGO-CaCl2 inks and mGO cellulose composite inks.